Oxford international primary english student book for grade 3 - Barber, Alison (Karachi: Oxford University Press., 2022)
The Oxford International Primary English: Student Book for Grade 3 is designed to build core literacy skills in young learners through a variety of engaging texts, activities, and exercises. The book introduces students to key concepts in reading, writing, listening, and speaking, with a focus on developing comprehension and vocabulary. Through fiction, non-fiction, poetry, and informational texts, students are encouraged to think critically, express themselves clearly, and explore diverse genres. The book also emphasizes grammar, punctuation, and spelling, preparing students for more advanced language study. It provides a global perspective, making learning relevant and accessible to children from diverse backgrounds.